Genetic Engineering as a Strategy to Improve the Therapeutic Efficacy of Mesenchymal Stem/Stromal Cells in Regenerative Medicine - Damasceno, Patricia Kauanna Fonseca; de Santana, Thaís Alves; Santos, Girlaine Café; Orge, Iasmim Diniz; Silva, Daniela Nascimento; Albuquerque, Juliana Fonseca; Golinelli, Giulia; Grisendi, Giulia; Pinelli, Massimo; Ribeiro dos Santos, Ricardo; Dominici, Massimo; Soares, Milena Botelho Pereira (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem/stromal cells (MSCs) have been widely studied in the field of regenerative medicine for applications in the treatment of several disease settings. The therapeutic potential of MSCs has been evaluated in studies in vitro and in vivo, especially based on their anti-inflammatory and pro-regenerative action, through the secretion of soluble mediators. In many cases, however, insufficient engraftment and limited beneficial effects of MSCs indicate the need of approaches to enhance their survival, migration and therapeutic potential. Genetic engineering emerges as a means to induce the expression of different proteins and soluble factors with a wide range of applications, such as growth factors, cytokines, chemokines, transcription factors, enzymes and microRNAs. Distinct strategies have been applied to induce genetic modifications with the goal to enhance the potential of MCSs. This review aims to contribute to the update of the different mechanisms employed for MSCs genetic modification, as well as the factors investigated in different fields in which genetic engineered MSCs have been tested.